A calcium antagonist, nifedipine, modifies exercise-induced asthma. Issue 10 (October 1981) - Barnes, P J; Wilson, N M; Brown, M J
Abstract : In eight extrinsic asthmatic subjects (age range 16-38 years) there was a significant reduction (p less than 0.01) in the severity of bronchoconstriction after a treadmill exercise test performed 30 minutes after nifedipine 20 mg sublingually. The maximum fall in peak expiratory flow after exercise was 36.0 +/- SEM 5.3% compared with a maximum fall of 56.5 +/- 4.1% after matched placebo capsules when given in double-blind randomised manner on separate days. There was no significant resting bronchodilation or change in blood pressure or heart rate after nifedipine. there was a significant rise in venous plasma histamine during exercise with placebo (6.1 +/- 0.8 to 13.5 +/- 3.5 nmol/l, p less than 0.01) but no significant increase with nifedipine (4.6 +/- 0.6 to 4.7 +/- 0.6 nmol/l) suggesting that nifedipine inhibits the release of mast cell mediators. The dose of inhaled histamine which provoked a 20% fall in peak expiratory flow was also significantly higher (p less than 0.05) with nifedipine (1.5 +/- 0.31 mg/ml) compared with placebo (2.7 +/- 0.63 mg/ml), indicating that there is a small inhibitory effect on bronchial smooth muscle contractility. Nifedipine is a potent antagonist of calcium ion influx in smooth muscle and secretory cells, and these studies suggest that it may inhibit release of mast cell mediators and reduce bronchial smooth muscle contractility in asthma.